The Law Concept of Sharia Banking Compliance on Murabaha Financing in Indonesia - Ghozali, Mohammad; Sup, Devid Frastiawan Amir; Prastyaningsih, Ika; Adan, Hasanuddin Yusuf (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
Submission to sharia is a fundamental factor which discriminates sharia banking from the conventional one. Therefore, sharia banking as intermediating institution and provider of financial services which base their operation on Islamic sharia values have to ensure their compliance towards sharia principles. Besides, sharia banking applies profit sharing principle as the main foundation in fund collection, fund distribution, and financing. A product dominating and attracting customers the most is murabaha. This product still receives tough critics from scientists, though, so that this research aims at investigating sharia banking compliance on murabaha financing viewed from the perspective of fatwa from DSN-MUI. This research applies qualitative design with normative approach (DSN-MUI fatwa). The result of the study shows that murabaha contract in Indonesian sharia banking must fulfill sharia compliance stated in the Qur’an, Sunnah, Regulation of Bank of Indonesia, and DSN-MUI fatwa.